2010
DOI: 10.1155/2010/939536
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Behaviour of Chitosan

Abstract: Chitosan, a versatile biopolymer, finds numerous applications in textile processing unit operations such as preparation, dyeing, printing, and finishing. However, the accessibility of this biopolymer by the textile material depends on the viscosity of its solution which in turn is a function of its molecular weight. In this work, therefore, the effect of molecular weight, storage life, presence of electrolyte, and particle size of chitosan on its viscosity was investigated. Chitosan of different molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 21 publications
5
60
1
2
Order By: Relevance
“…A decrease in mechanical properties may be associated with higher ionic strength resulted from introduction higher amount of β-GP ions in formulation F4. This observation is consistent with literature wherein the addition of ions was one of the crucial parameters responsible for loosening the CS hydrogels' structure and decreasing the viscosity [37,43].…”
Section: Viscosity and Mechanical Measurementssupporting
confidence: 93%
See 1 more Smart Citation
“…A decrease in mechanical properties may be associated with higher ionic strength resulted from introduction higher amount of β-GP ions in formulation F4. This observation is consistent with literature wherein the addition of ions was one of the crucial parameters responsible for loosening the CS hydrogels' structure and decreasing the viscosity [37,43].…”
Section: Viscosity and Mechanical Measurementssupporting
confidence: 93%
“…The observed ability to gradually recover It was found that ion crosslinked CS formulations F3 and F4 displayed lower viscosities compared with unmodified CS hydrogels (Table 3). A significant drop (almost 2-fold) in viscosity of hydrogel F4 (in comparison to F2) was probably affected by greater ionic strength resultant from addition of higher amount of β-GP [37]. The rheological behavior was found to be comparable between the samples investigated at room and body temperature.…”
Section: Viscosity and Mechanical Measurementsmentioning
confidence: 89%
“…The powdered sample was finally sieved to obtain a sample with a particle size of 30-100 mm and was stored. To prepare chitosan solution, 1 g of chitosan (medium molecular weight) was dissolved in 1.5 ml acetic acid (96%) and 10 ml distillated water at temperature 30 C [17]. The mixture was stirred for 24 h to reach a homogeneous mixture.…”
Section: Materials and Preparation Approachmentioning
confidence: 99%
“…[3]. Впоследствии его объясняли либо кислотным гидролизом гликозидных связей (деструкцией) [2,[4][5][6][7][8], либо другими причинами: медленным образовани-ем внутримолекулярных водородных связей с уплотнением клубков [9,10], компактизацией макромолекул хитозана [11], снижением степе-ни структурированности растворов [12], пере-стройкой надмолекулярной структуры раствора [13], процессами структурной перестройки [14,15], агрегации [16], биодеградации [17]. Одна-ко авторы работы [2] замечают, что изменение конформаций макромолекул и степени структу-рирования не может приводить к практически полному разжижению концентрированных рас-творов полимера при длительном хранении.…”
Section: Introductionunclassified